Changes in University Club Athletes' and Non-Athlete Students' Stress and Perceived Gains Across a Semester. Issue 1 (April 2021) - Martin, Eric A.; Unfried, Alana; Kim, Steven; Beckham, George K.
To examine the relationship between club rugby participation, collegiate experiences, and perceived gains, 25 rugby players and 25 non-athlete students completed the Student-Athlete Experiences Inventory-Revised, Student-Athlete Gains Inventory, and Perceived Stress Scale at the start and end of a semester. A RM-ANOVA and partial-η 2 effect sizes determined if group and time differences were present. We selected variables associated with the post-scores for practical and liberal arts gains with the lasso method. Rugby players engaged in more diverse social interactions (partial-η 2 = 0.091) and were more actively involved on campus (partial-η 2 = 0.0914) than non-athlete students, but paradoxically had lower practical arts gains ( p < 0.0001). All students reported increasing stress levels from start to end of the semester (partial-η 2 = 0.109), which contributed to decreasing practical arts gains. Students need help with stress management near semester's end. Club rugby players should seek support services on campus to improve career preparedness.